2001
DOI: 10.1257/aer.91.2.328
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Country Technology Diffusion: The Case of Computers

Abstract: After controlling for the above-mentioned variables, we do not Þnd an independent role for the English-(or European-) language skills of the population. The quantitative importance of these Þndings, as well as their theoretical interpretation, is discussed in the concluding section. Data on Computer ImportsThe focus of our analysis is computer investment per worker. We measure aggregate computer investment by imports of computer equipment. Almost all countries in the World report detailed information on their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(107 citation statements)
references
References 17 publications
4
82
0
2
Order By: Relevance
“…Using data from a survey of 2,139 enterprises from 10 middle and high-income countries, Kraemer et al (2002) show that enterprises that are more internationalized (in terms of operations, sales and inputs) are more likely to engage in business-to-business e-commerce, but not in businessto-consumer e-commerce. Caselli and Coleman (2001) show that ICT investment is higher in countries that import more manufactured goods from countries in the OECD. Muller and Salas (2003) find that the number of personal computers but not the number of Internet users and hosts is correlated with imports.…”
Section: Export Behavior and Internet Usementioning
confidence: 99%
See 2 more Smart Citations
“…Using data from a survey of 2,139 enterprises from 10 middle and high-income countries, Kraemer et al (2002) show that enterprises that are more internationalized (in terms of operations, sales and inputs) are more likely to engage in business-to-business e-commerce, but not in businessto-consumer e-commerce. Caselli and Coleman (2001) show that ICT investment is higher in countries that import more manufactured goods from countries in the OECD. Muller and Salas (2003) find that the number of personal computers but not the number of Internet users and hosts is correlated with imports.…”
Section: Export Behavior and Internet Usementioning
confidence: 99%
“…Countries with greater contact, either via trade, tourism, or geographical location, with the outside world, are more likely to be advanced in digital technology than other countries.'' Similarly, Caselli and Coleman (2001) argue that countries open to imports from high-income Organisation for Economic Co-operation and Development (OECD) economies will benefit from knowledge spillovers and, hence, be more likely to adopt new technologies.…”
Section: Export Behavior and Internet Usementioning
confidence: 99%
See 1 more Smart Citation
“…In principle, our instruments -the spread of the traditional telephone and cable networks -may not only affect the deployment of the broadband network but also the diffusion of other growth-enhancing technologies, such as mobile telephony (Gruber and Verboven, 2001;Koski and Kretschmer, 2005) and computers (Caselli and Coleman, 2001). To test this claim, we consider mobile telephony and computers which also diffused rapidly in the 1990s.…”
Section: Tests For Instrument Validity and Robustnessmentioning
confidence: 99%
“…Copeland and Taylor [18] concluded that FDI affect the host environment from three ways, including scale effect, structure effect and technology effect; Dean et al [19], Eskeland and Harrison [13] argued that the foreign capital can weaken the damage to the environment through technology diffusion effect; Caselli and Coleman [20] showed that developing countries hoped that environment friendly enterprise from technical leader bring in advanced technologies, but the absorption and application capabilities of such environmental friendly technologies are limited to the level of human capital of the country or region. Therefore, the level of human capital can affect the ability of the country or region to absorb the advance technologies, including emission reduction technology [21].…”
Section: Literature Reviewmentioning
confidence: 99%